Влияние режимов обработки на зеренную структуру ферритно-мартенситной стали ЭП-823 - Линник, Валерия Васильевна (Перспективы развития фундаментальных наук. Т. 1 : сборник научных трудов XIX Международной конференции студентов, аспирантов и молодых ученых, 26-29 апреля 2022 г.)
The effect of high-temperature thermomechanical treatment (HTMT) with plastic deformation by rolling in austenitic region on the grain structure of 12% chromium ferritic-martensitic steel EP-823 were studied. The features of the grain structure of steel are studied by optical metallography. It is shown that HTMT leads to the formation of structure with grains flattened in the rolling plane and extended in the rolling direction. The average grain size after HTMT in a plane parallel to the rolling plane is higher than after THT, and in the rolling plane it is smaller than after THT.